Late Permian appinite–granite complex from northwestern Liaoning, North China Craton: Petrogenesis and tectonic implications - Zhang, Xiaohui; Xue, F.; Yuan, L.; Ma, Y.; Wilde, Simon (Elsevier BV, 2012)
The appinite–granite suite commonly occurs within post-subduction regimes during the final stage of anorogeny and thus holds the key to monitoring critical geodynamic and crustal evolutionary processes. The present zircon U–Pb dating and geochemical study documents the Late Permian appinite–granite complex from northwestern Liaoning, North China Craton. The hornblende-rich appinitic rocks have an SiO2 range from 41.8 to 53.4%, moderate to high alkali contents, enrichment in large ion lithophile elements and depletion in high field strength elements, with initial 87Sr/86Sr ratios of 0.7066 to 0.7128, εNd(t) of -8.3 to -13.3 and zircon εNd(t) from -10.1 to -18.7. These features suggest that their generation most likely involves metasomatism of mantle peridotites by sediment-derived liquids related to subduction and a later partial melting. The associated monzogranites range in SiO2 from 72.6 to 75.0% and exhibit a high-K calc-alkaline character, with high Sr–Ba abundances and elevated Sr/Y and La/Yb ratios. Such potassic adakitic signatures, plus their evolved isotopic compositions (87Sr/86Sri=0.7063 to 0.7066, εNd(t)=-15.6 to -16.3, zircon εNd(t)=-16.5 to -18.8), are consistent with partial melting of mixed protoliths including newly underplated enriched mafic lower crust and minor old lower crustal materials. Such a mafic and felsic magma association not only attests to a heterogeneously enriched sub-continental lithospheric mantle beneath the northern North China Craton, but also indicates reworking within a post-orogenic transcurrent regime of lithospheric delamination. The temporal coincidence of the present appinite–granite complex with regional transcurrent fault activity leads to the further suggestion that such mafic–felsic magmatic suites could provide spatial markers for monitoring important post-orogenic structural and geodynamic processes.